Media Pembelajaran Peta Berbasis Web untuk Meningkatkan Minat Belajar Siswa - Otoluwa, Yemima; Sumarmi, Sumarmi; Bachri, Syamsul (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
This research is a research and development that produces learning media based on the media feasibility and effectiveness. The resulting product is a web-based map learning media on the material of Geographic Information Systems at Grade XII. This research used the ADDIE development model (Analysis, Design, Development, Implementation, & Evaluation). The instrument used was a questionnaire for validators, teachers, and students. The results of the validation test were 89.56% with valid criteria, which means a trial can be carried out. The results of the student trial obtained a score of 86.58%, while the average student learning outcome was 83.75% and the results of the teacher's trial obtained a score of 95%. The results were categorized into effective criteria. Thus, the media can be used properly.